Characterization in children 6 years of age with tooth interference of primary schools - Hechavarría- Martínez, Barbara (2018)
Characterize children from 6 years of age in primary schools belonging to the health area of the Policlinico Docente "30 November". Methods: He was an observational study descriptive and cross-sectional aiming to. The universe was composed of 83 children whose dental care is carried out in the Department of Stomatology of the Policlinico teacher "30 de Noviembre", in the period between June of 2017 and 2018 April. The data was an interview structured to parents or guardians, in order to obtain data accurate and verified, using as a summary measure the percentage and reflecting the data in contingency tables. He was the oral test to children using the tongue depressor and natural or artificial light. Results: The study dominated the female sex. The most practiced disfiguring habits were postural habits and digital suction. Conclusions: Most found anomaly was one-sided after reversed occlusion. Taking into account this recommended expanding research in other schools, since these results alert us to the need to intercept the tooth interference from an early age.